Citizens Groups as Local Democracy Actors in Serbia - Matić, Petar (Serbian political thought, 2024)
The aim of this paper is to highlight the role citizens’ groups as democracy actors at the local level of governance. The author uses the statistical data analysis method and available findings related to the local elections’ results in Serbia between 1992 and 2022. In the introduction, the author identifies the main assumptions of local democracy as the basis of a broader, society-wide democratization.  The importance of local self-government and elections for the lowest instance the vertical organization of power is also addressed. The paper points to the normative framework regulating the establishment and action of citizens’ groups on the political stage. In the central part of the paper, results of citizens’ groups are analyzed for each election cycle, along with their participation in coalitions and exercise of local authority. The conclusion seeks to answer the research question raised and to provide some recommendation for the empowerment of citizens’ groups as authentic local democracy actors.
Keywords: local democracy; local elections; citizens' groups; democratization; local political actors; local authorities